(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article discusses the compound terms used in the field of Uzbek radio communication. Analysis, synthesis, component analysis methods were used during the analysis. The components of field terms are divided into types according to their quantity and studied, and each type is explained by the example of field terms.